Anthriscus lamprocarpa subsp chelikii (Apiaceae), a new subspecies from southern Turkey - Tekin, Mehmet; Civelek, Semsettin (Magnolia Press, 2016)
During the revisionary study of members of the genus Anthriscus (Apiaceae) distributed in Turkey, we came across a taxon of the section Cacosciadium. In the morphological studies, the principal characteristics of this plant suggested that it belonged to A. lamprocarpa. However, some considerable morphological differences were found, such as filament length and fruit size and surface characteristics, which clearly differed from those of the typical A. lamprocarpa. On the basis of the longer filament, longer and narrower fruits, dimorphic ornamentation of fruit surface, and also the lack of lacquered fruit surface, we describe a new subspecies, A. lamprocarpa subsp. chelikii, which is distributed in southern Turkey. Diagnostic characteristics with regard to other taxa within A. sect. Cacosciadium are discused.
Keywords: Anthriscus; Anthriscus sylvestris; Cacosciadium; plant morphology; taxonomy; Umbelliferae